(untitled) (TAMADDUN NURI JURNALI, 2024)
This article discusses the role and importance of small business and private entrepreneurship in the economic development of Khorezm region, the role of small business and private entrepreneurship in the national economy. It analyzes the measures taken to develop the economic potential of the Khorezm region and their results in the field of small business and private entrepreneurship.